A case of mononucleosis in an anorexic patient with zinc deficiency - Russo, Vincenzo (Progress in Nutrition, 2014)
We report the case of  a 24 years old women with anorexia nervosa (BMI= 14.3 Kg/m2 ) and recent infection by virus of mononucleosis. The patient had remittent fever, sore throat, hepatosplenomegaly, laterocervical lymphoadenopathy. Biochemical and serological work-out showed absolute lymphocytosis and antibodies against capsidic and nuclear Epstein-Barr virus antigens. Morover, we have found reduced serum zinc levels. This feature, in the context of anorexia nervosa, contributed to worsen the clinical picture of the concomitant viral infection.